1985
DOI: 10.3109/15513818509026902
|View full text |Cite
|
Sign up to set email alerts
|

Primitive Cystic Hepatic Neoplasm of Infancy with Mesothelial Differentiation: Report of a Case

Abstract: A malignant cystic neoplasm in the liver of a 6-month-old girl is reported. The neoplasm has unique clinical and morphological features, and despite ultrastructural and immunohistochemical studies, the tumor could not be clearly classified as any known primary hepatic neoplasm of infancy. A differentiated cystic component of the neoplasm had features of cystic peritoneal mesothelioma. Alpha-1-antitrypsin and alpha-fetoprotein were demonstrated in solid, anaplastic portions of the recurrent tumor by immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Furthermore, one patient reported in the literature that did not receive any treatment died from the disease 12 years after diagnosis [2]. Another patient reported with an initial diagnosis of cystic mesothelioma died of diffuse malignant mesothelioma 11 months later [3]. Additional evidence of a benign to malignant transformation of peritoneal cystic mesothelioma is provided by the following case report.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Furthermore, one patient reported in the literature that did not receive any treatment died from the disease 12 years after diagnosis [2]. Another patient reported with an initial diagnosis of cystic mesothelioma died of diffuse malignant mesothelioma 11 months later [3]. Additional evidence of a benign to malignant transformation of peritoneal cystic mesothelioma is provided by the following case report.…”
Section: Introductionmentioning
confidence: 71%
“…There has been only one other case reported that described a similar phenomenon [3]. The patient was a 6-month-old infant diagnosed with a cystic lesion growing into the liver parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,12,16,26 The clinical course of BMM is usually benign. No metastasis, but rare malignant transformation 16,18,19 and death 6 have been documented. BMM occurs more commonly in females (87%), particularly in the pelvic area of the cul-desac, uterus, and rectum.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that cautions should be made in the assessment of this condition as a ''benign'' process. This is mainly because of the high recurrence rate (27-75%) and because of the reported transition to conventional MPM [41][42][43][44].…”
Section: Differentiation Of Mpm From Benign Mesothelial Lesionsmentioning
confidence: 99%